Normal ballistocardiography - Silicani, Armando (1953)
Many years ago, just since 1877, in a case of Bright's Disease, Gordon was able to record body movements due to the impacts of cardiac contraction, blood circulation and propagation. Thus, this phenomenon entered the atmosphere of scientific knowledge.